Retinopathy in Youth With Type 2 Diabetes Participating in the TODAY Clinical Trial (American Diabetes Association, 2013)
OBJECTIVE: To determine the prevalence of retinopathy in 517 youth with type 2 diabetes of 2–8 years duration enrolled in the TODAY study. RESEARCH DESIGN AND METHODS: Retinal photographs were graded centrally for retinopathy using established standards. RESULTS: Retinopathy was identified in 13.7% of subjects. Prevalence increased with age, diabetes duration, and mean HbA(1c). Subjects in the highest BMI tertile had the lowest prevalence of retinopathy. CONCLUSIONS: Prevalence of retinopathy and its association with HbA(1c) and diabetes duration is similar to that previously reported in youth with type 1 diabetes and in adults with type 2 diabetes of known duration. The mechanism underlying the reduced risk of retinopathy in the most obese individuals is unknown. Follow-up of this cohort will help define the natural history of retinopathy in youth with type 2 diabetes.